Somatic responses of injured Siamese fighting fish (Betta splendens) raised using various recipes of Thai herbal fermented water - Malawa, Saowalak; Nuntapong, Nutt; Thongprajukaew, Karun (Agriculture and Natural Resources, 2024)
Importance of the work: Thai herbal remedies offer an alternative to chemicals to help in the recuperation of injured Siamese fighting fish (Betta splendens). Objective: To evaluate fish survival and growth, feed utilization, skin coloration, digestive enzyme activity, muscle quality and whole-body composition at the end of herbal treatment for 5 wk. Materials & Methods: Each male fighting fish had one-half of its caudal fin amputated and then was allocated to one of nine experimental groups. Each fish was reared separately for 5 wk in its own small tank. Treatments consisted of two controls, with one using non-fermented water (CT 1), while the other control consisted of fermented water (CT 2) and was mixed with various products—dried lemongrass leaves (1 g/L), dried clay (50 g/L) and salt (5 g/L). Subsequently, CT 2 was added to different combinations of dried Indian almond leaves (0.25 g/L), dried banana leaves (1.5 g/L) or dried papaya leaves to make seven other treatments. Results: No mortality occurred and fish growth performance was not influenced by the herbal treatments. The feed conversion ratio significantly (p < 0.05) increased in association with decreasing amylase-specific activity, whereas protein- and lipid-digesting enzymes remained consistent. Skin coloration parameters were either reduced or preserved due to the herbal treatments. Muscle quality was unchanged, whereas the crude protein, crude lipid and ash contents in whole-body were similar across the nine treatments. Main findings: Whereas entire fish can compensate for growth normally, these findings indicated minor effects of long-term herbal treatments on the somatic changes in the injured fish. The results endorsed the therapeutic approach of fermented water of Thai herbs in Siamese fighting fish.